Glial Patchwork: Oligodendrocyte Progenitor Cells and Astrocytes Blanket the Central Nervous System - Barber, Heather M.; Ali, Maria F.; Kucenas, Sarah (Frontiers in Cellular Neuroscience, 2022)
Tiling is a developmental process where cell populations become evenly distributed throughout a tissue. In this review, we discuss the developmental cellular tiling behaviors of the two major glial populations in the central nervous system (CNS)—oligodendrocyte progenitor cells (OPCs) and astrocytes. First, we discuss OPC tiling in the spinal cord, which is comprised of the three cellular behaviors of migration, proliferation, and contact-mediated repulsion (CMR). These cellular behaviors occur simultaneously during OPC development and converge to produce the emergent behavior of tiling which results in OPCs being evenly dispersed and occupying non-overlapping domains throughout the CNS. We next discuss astrocyte tiling in the cortex and hippocampus, where astrocytes migrate, proliferate, then ultimately determine their exclusive domains by gradual removal of overlap rather than sustained CMR. This results in domains that slightly overlap, allowing for both exclusive control of “synaptic islands” and astrocyte-astrocyte communication. We finally discuss the similarities and differences in the tiling behaviors of these glial populations and what remains unknown regarding glial tiling and how perturbations to this process may impact injury and disease.